Energy Action Mechanism of Coal and Gas Outburst Induced by Rockburst - Wenqing Zhang; Chaomin Mu; Dengke Xu; Zhongqing Li (Shock and Vibration)
The essence of both rockburst and coal and gas outburst lies in fast energy release. In order to explore the energy action mechanism of coal and gas outburst induced by rockburst in rockburst and coal and gas outburst combined mines, the split Hopkinson pressure bar (SHPB) experimental device was firstly used to conduct uniaxial impact failure test of coal specimens prone to outburst under different strain rates, and their energy dissipation laws under impact loading were obtained. Next, under the engineering background of coal and gas dynamic phenomena induced by rockburst with different intensities in Xinyi Coal Mine and Pingdingshan Coal Group No. 12 Colliery in Henan Province and Dingji Coal Mine of Huainan Mining Group in Anhui Province, experimental study results were combined with numerical simulation analysis to discuss the energy mechanism of coal and gas outburst induced by rockburst. The study results show that the outburst can be divided into two different processes—critical outburst and outburst—according to the evolution law of outburst energy, and the critical energy conditions for coal and gas outburst are proposed. The minimum destructive energy range for the critical outburst of coal mass is obtained as (5–10) × 104 J/m3. Under some low gas, high stress, or strong disturbance conditions, applied loads can become the main energy sources causing critical failure and even crushing and throwing of coal mass. The coal mass will present an interval splitting structure under dynamic loading, which is obviously different from the failure mode of coal mass under static actions.